Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan Pada PT. Kurnia Aneka Gemilang Tanjung Morawa - Reza Nurul Ichsan; Lukman Nasution (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine the effect of service quality and price on customer satisfaction. at PT. Kurnia Aneka Gemilang Tanjung Morawa. Methods of data collection by means of questionnaires. Methods of data analysis using multiple linear regression method. The results showed that partially variable quality of service and price significantly influence customer satisfaction. Each increase in service quality weight of 1 will increase customer satisfaction by 0.423. Any increase in price weight of 1 will increase the weight of customer satisfaction by 0.305. Simultaneously variable quality of service and price have a significant effect to customer satisfaction. F-count value is 31,253, while F-table 0,05 is 3,124, because F-count is bigger than F-table then it is concluded simultaneously variable of service quality and price have significant effect to customer satisfaction at 95% confidence level. The coefficient of determination obtained at 0.450, which means 45.00% of changes in customer satisfaction in the company can be explained by changes in service quality and price variables, while the remaining 55.00% is explained by other variables that are not included as variables in the study.